Superconducting and electrical transport properties of (Bi1.4Pb0.6)Sr2Ca2Cu3O10 with nano-co0.5Ni0.5Fe2O4 addition - Muhammad Hafiz, Mazwir; R., Abd-Shukor (2018)
The effects of nano-CoFe2O4 addition on the superconducting and transport properties of (Bi1.4Pb0.6)Sr2Ca2Cu3O10 high temperature superconductor (Bi-2223) were studied. Bi-2223 superconductor samples were prepared using co-precipitation method. 0.01 to 0.05 wt.% of Co0.5Ni0.5Fe2O4 magnetic nanoparticles with average size of 20 nm was added to enhance the flux pinning and improve the transport properties of the Bi-2223 superconductor [1-2]. The Co0.5Ni0.5Fe2O4 particle size is larger than the coherence length, ξ and smaller than the penetration depth, λ of Bi-2223 (ξ = 2.9 nm, λ = 60 – 1000 nm for Bi-2223 [3]). The critical temperature (Tc), critical current density (Jc), phase formation and microstructure of the samples were investigated. As shown in Fig. 1, all samples with addition of nano-Co0.5Ni0.5Fe2O4 showed higher Jc compared to non-added sample. The sample with 0.01 wt.% addition showed the highest Tc and Jc. A higher amount of addition (>0.01 wt.%) leads to degradation of both Tc and Jc. This study shows that small addition of Co0.5Ni0.5Fe2O4 nanoparticles can effectively enhance the transport critical current density in Bi-2223 superconductor.